Implementation Strategy for Dengue Vaccine Rollout in Bangladesh: Challenges and Opportunities - Huq, Hiya; Anzoom, Jarin; Begum, Munira; Sweety, Afroza Akbar; Sultana, Khadiza; Kumar, Pobitro (International Journal of Human and Health Sciences (IJHHS), 2026)
One of the recent evidence-based interventions for dengue prevention is the tetravalent dengue vaccine TAK-003, which can play a vital role in reducing both the incidence and severity of dengue infections in endemic regions like Bangladesh. This vaccine can serve as a complex, multilevel intervention targeting primary prevention by immunizing individuals against all four dengue virus serotypes. By reducing the incidence of dengue infections, TAK-003 provides a preventive strategy that complements traditional vector control efforts. This paper aims to discuss implementation strategy for dengue vaccine rollout in Bangladesh. Implementing a school-based dengue vaccination program in Bangladesh involves tackling challenges like vaccine hesitancy, misinformation, and broader health behaviour determinants. Ensuring acceptance of the dengue vaccine, such as TAK-003, is crucial, as concerns about safety and misinformation can influence public perception. We also have proposed a multi-level, evidence-based intervention for dengue prevention among school-going children (aged 5–16 years) in Bangladesh, which has been structured around the Behaviour Change Wheel (BCW). It has included key components such as vaccination, vector control, school-based awareness campaigns, early diagnosis, and digital health interventions. These components aim to address factors influencing Capability, Opportunity, and Motivation. Implementing such a complex intervention in a low-resource setting like Bangladesh necessitates a critical feasibility assessment. The BCW’s APEASE framework (Affordability, Practicability, Effectiveness, Acceptability, Side Effects, and Equity) could be used for this evaluation. This approach ensures that the intervention is not only theoretically sound but also adaptable to the Bangladeshi context, making it affordable, practical, and effective while addressing potential ethical concerns, including equity and community acceptability. International Journal of Human and Health Sciences Vol. 10 No. 02 Apr’26 Page: 71-77